Pancreaticoduodenectomy for pancreas carcinoma occurring in the annular pancreas: report of a case - Kawaida, Hiromichi (Clin J Gastroenterol, 2015)
The annular pancreas is a rare congenital anomaly in which a ring of the pancreas parenchyma surrounds the second part of the duodenum. Malignant tumors are extremely rare in patients with an annular pancreas. A 64-year-old man presented with appetite loss and vomiting. Abdominal contrast-enhanced computed tomography (CT) indicated pancreas parenchyma surrounding the second part of the duodenum, and a hypovascular area occupying lesion in the annular pancreas. Subtotal stomach-preserving pancreaticoduodenectomy was performed. Histopathology showed pancreatic carcinoma occurring in the complete annular pancreas.